Injuries in young female players in European team handball - Wedderkopp, N.; Kaltoft, M.; Lundgaard, B.; Rosendahl, M.; Froberg, K. (Scandinavian Journal of Medicine & Science in Sports, 1997)
The purpose of this study was to examine the nature, extent and severity of sports injuries in young female players in European team handball and to identify the etiological factors involved in the injuries. Twenty-two teams with 217 players, aged 16-18 years, participated in the study. A very high injury incidence during games was observed, with 40.7 injuries/1000 hours of game. Backplayers had the highest incidence (54.8/1000 hours), which is five times higher than any previously recorded injury incidence in players in European team handball. We found that 92.9% of injuries were traumatic and 7.1% were from overuse. One-hundred and twenty-four of the 211 injuries were traumatic injuries of the lower extremities. Of these 63 (51%) were without contact with an opponent. The study confirmed that European team handball is a sport that has a very high injury rate, especially regarding young female players. Field position and earlier injuries are major risk factors, with an earlier injury being the single highest risk factor and with backplayers having a significantly higher number of injuries than players in other field positions.